KURIKULUM PENDIDIKAN ANAK USIA DINI BERBASIS BUDAYA LOKAL DAN KEARIFAN NUSANTARA: TINJAUAN SISTEMATIS DAN IMPLIKASINYA TERHADAP IDENTITAS NASIONAL - Wiwin Setiani; Kartika Fajriani; Lina Revilla Malik (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze and synthesize a curriculum model for early childhood education based on local culture and the wisdom of the Nusantara, as well as its implications for the formation of national identity. The method used is a systematic literature review, examining various research findings related to the implementation of curricula based on local wisdom in various regions of Indonesia. The analysis was conducted through a process of identifying, classifying, and synthesizing research findings to identify general patterns and characteristics of the evolving curriculum models. The results indicate that the integration of local wisdom into the curriculum is carried out holistically through learning objectives, content, processes, and assessment using thematic and project-based approaches. This implementation has been proven to increase children’s engagement, optimize social-emotional, cognitive, and motor development, and strengthen character and cultural identity from an early age. Furthermore, learning based on local culture makes the educational process more contextual and relevant to children’s lives, while also playing a role in instilling national values and preserving cultural sustainability amidst the challenges of globalization